The TDHF code Sky3D - Maruhn, J. A.; Reinhard, Paul-Gerhard; Stevenson, P. D.; Umar, A. S. (Computer Physics Communications, 2014)
The nuclear mean-field model based on Skyrme forces or related density functionals has found widespread application to the description of nuclear ground states, collective vibrational excitations, and heavy-ion collisions. The code Sky3D solves the static or dynamic equations on a three-dimensional Cartesian mesh with isolated or periodic boundary conditions and no further symmetry assumptions. Pairing can be included in the BCS approximation for the static case. The code is implemented with a view to allow easy modifications for including additional physics or special analysis of the results. © 2014 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-07-24
Keywords: BCS; Density-functional theory; Giant resonances; Hartree-Fock; Heavy-ion collisions; Skyrme energy functional